Behavior of RC beams retrofitted in shear using coir and flax fiber reinforced polymer composites - Mandoria, Pratyush Kumar (My University, 2019)
Worldwide, a great deal of research is currently being carried out concerning the use of fiber reinforced plastic wraps, laminates, sheets in repair and strengthening of reinforced concrete beams. FRP application is a very effective way to repair and strengthen structures that have become structurally weak over their life span. FRP repair system provide an economically viable alternative to traditional repair system and materials. Experimental investigation on shear behavior of RC beams strengthened using natural fibers, coir fiber and flax fiber reinforced polymer sheets are carried out. Externally reinforced concrete beams with epoxy bonded CFRP and FFRP sheets were tested to failure using symmetrical two-point loading system. Eight beams were casted out of which 2 beams were control beams, Other 6 beams were retrofitted using varying combination of the fiber and wrapping technique. Experimental data on load and deflection of each of the beams were obtained. The detailed procedure and application of CFRP and FFRP for shear strengthening of RC beam is also includ
Keywords: retrofitting; coir; flax; shear; RC beams